KONTRIBUSI SYAIR ACHMAD SYAUQI BAGI PERKEMBANGAN ANAK - Annisa Mutiara Rj, Eva Farhah (CMES (Center of Middle Eastern Studies), 2017)
This research tries to find the text structure and also the personal and educational values of a children poem by Achmad Syauqi (1868-1932 M) entitled “Sulaimān wath-Thāwūs”. The theory used is Michael Riffaterre’s semiotic. It is a discipline which studies system, rules, and conversions which enables to see the meaning of the sign. The method used is descriptive qualitative, which explains data in form of word, phrases, sentences, or expressions in the text. Not only that this research also reveals the personal and educational values of the text. In this case the purpose of this research is first, to explain the poem’s text structure and second, to reveal the personal and educational values as contribution to children poems. It is found that the text structure of “Sulaimān wath-Thāwūs”  has a single relation between elements so it gives a clear meaning. The personal and educational values given in the text “Sulaimān wath-Thāwūs” includes emotional growth, intelligent, imaginations, ethical and religious growth, exploration, language, aesthetic values and reading habit.